Pengaruh Disiplin Kerja dan Beban Kerja terhdap Kinerja Karyawan (Studi pada Buruh Panen Kelapa Sawit PT. Damai Jaya Lestari Afdeling IX Kecamatan Tanggetada, Kab. Kolaka) - Almansyah Rundu Wonua; Hendrik Hendrik; Andi Suci Magfi Rahmadani (STIKes Ibnu Sina Ajibarang, 2023)
This research is entitled the Influence of Work Discipline and Workload on Employee Perfomoance (Study Of Palm Oil Harvest Workers At PT. Damai Jaya Lestari Afdeeling IX Tanggetada Sub-Distric, Kolaka District). The purpose of this study is to determine: (1) The effect of work discipline on employee performance PT. Damai Jaya Lestari Afdeeling IX Tanggetada Sub-Distric, Kolaka District, (2) Effect of workload on employee performance PT. Damai Jaya Lestari Afdeeling IX Tanggetada Sub-Distric, Kolaka District. This study uses an approach with quantitative methods. Collecting data in this study using observation, documentation and questionnaires. The population of this study were all oil palm harvesting workers PT. Damai Jaya Lestari Afdeeling IX Tanggetada Sub-Distric, Kolaka District. While the sample in this study amounted to 60 workers by determining the sample using a census technique. Testing research instruments using validity and reliability test with SPSS 25.0. The data analysis technique used in this research is Struktural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the result of the study it is known that the work discipline variable has a positive and significant effect on employee performance as indicated by the P-Values of 0,005 and the workload variable has a positive and significant effect on employee performance as indicated by the P-Values of 0.005.